Evaluating the urban heat island phenomenon from a spatial planning viewpoint. A systematic review - Isola, Federica; Leone, Federica; Pittau, Rossana (TeMA - Journal of Land Use, Mobility and Environment, 2023)
The increasing rate of urbanization and continuous population growth in urban areas leads to several problems, including the emergence of urban heat islands (UHI), defined as urban areas where temperatures are higher than in the surrounding rural areas. UHIs have negative impacts on the health of populations and lead to increased energy consumption for cooling. One of the main causes of higher temperatures in urban areas and, therefore, the creation of UHIs is impervious surfaces, which in turn lead to poor thermal comfort in cities. Ecosystem services and, in particular, the ecosystem service of local climate regulation are valuable tools to mitigate the effects of UHI. The contribution reviews the existing literature concerning the mitigation of heat island effects through ecosystem services, in order to understand how they are studied and analyzed in the international scenario. The proposed methodological approach is based on a framework of analysis of the scientific contributions published in the last fifteen years on the subject of UHI, investigating the phenomenon through an interpretation key based on the issues addressed, the methods used and the spatial scales to which these methods have been applied.